2019
DOI: 10.21307/ane-2019-001
|View full text |Cite
|
Sign up to set email alerts
|

Distinct classes of low frequency ultrasonic vocalizations in rats during sexual interactions relate to different emotional states

Abstract: This study examined low-frequency ultrasonic vocalizations (lUSVs) in rats during two types of sexual interactions: postejaculatory interval (PEI) and barrier-noncontact (NC) test. We report distinct classes of lUSVs that can be assigned to different emotional states; relaxation vs. frustration. Totally flat, 22-kHz calls (Class A), were observed during the relaxation state following ejaculation; characterized by immobilization or grooming during the PEI. On the other hand, two-three component lUSVs (Class B) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 62 publications
(93 reference statements)
0
20
0
Order By: Relevance
“…Acoustic analysis of the postejaculatory of 22 kHz vocalizations emitted by males during sexual contacts, or intended contacts, revealed that the calls are heterogenous and consist of long flat 22 kHz calls (20–35 kHz range) during the postejaculatory period, and anther class of 22 kHz calls. The other class of calls has higher sound frequency (23–45 kHz range) and some modulated frequency components that were observed during encounters of males with a female in a cage with a physical, perforated barrier, where animals could not have physical contact [ 157 ]. This last precopulatory category of calls would be compatible with a negative state of frustration caused by the presence of an inaccessible female, and not as a social detachment function [ 157 ] (for more details, see Section 2.8 and Section 3.5 ).…”
Section: Evolution and Functions Of Rat Vocalizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acoustic analysis of the postejaculatory of 22 kHz vocalizations emitted by males during sexual contacts, or intended contacts, revealed that the calls are heterogenous and consist of long flat 22 kHz calls (20–35 kHz range) during the postejaculatory period, and anther class of 22 kHz calls. The other class of calls has higher sound frequency (23–45 kHz range) and some modulated frequency components that were observed during encounters of males with a female in a cage with a physical, perforated barrier, where animals could not have physical contact [ 157 ]. This last precopulatory category of calls would be compatible with a negative state of frustration caused by the presence of an inaccessible female, and not as a social detachment function [ 157 ] (for more details, see Section 2.8 and Section 3.5 ).…”
Section: Evolution and Functions Of Rat Vocalizationsmentioning
confidence: 99%
“…Male rats emitted long 22 kHz vocalizations but with altered frequency structures (for acoustic details, see Section 2.5.2 , above) as compared to postejaculatory 22 kHz calls. These calls were associated with the exploration of holes in the barriers and were compatible with irritation and frustration [ 157 ]. These frustration calls were also observed in rat sexual encounters during unsuccessful mounting attempts or failed intromissions [ 148 ].…”
Section: Evolution and Functions Of Rat Vocalizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…An enhanced level of general arousal and sexual arousal before the termination of postejaculatory vocalizations can be distinguished by spectral analysis of postejaculatory calls. Before the termination of vocalizations, at the time as exploration or noncontact erection take place, some frequency modulations or a shift from about the 45-kHz to the 28-23-kHz band are more often detected, and these differ from the very flat 22-kHz frequency ultrasonic vocalizations at the beginning and middle of the postejaculatory period (Bialy et al, 2019).…”
Section: Postejaculatory Behaviormentioning
confidence: 99%
“…Furthermore, such vocalizations are present only in a familiar environment, and cues that increase anxiety level (odor cues from unfamiliar males) significantly reduce such postejaculatory vocalization (Bialy et al, 2016). Moreover, the postejaculatory vocalizations are distinct from shorter low-frequency vocalizations that are produced by a male rat expressing a sexually related frustration state (Bialy et al, 2019). Table 1 summarizes the key components of rat sexual behavior with relevant parameters that describe specific aspects of the behavior (first column).…”
Section: Rewarding Value Of Sexual Interactionsmentioning
confidence: 99%